The Nordbord usefulness in football: a systematic review of the pros and cons - Dimitrios Koukouras; Atharva Tere; Petros Koukouras; Monèm Jemni (Termedia Publishing House, 2024)
Since 2016 and the introduction of Nordbord to the world, a variety of sports and disciplines have used the device to inform everyday decision-making, such as post-match recovery, to assess players' readiness for the next fixture and mitigate the risk of injury. The objective of this paper was to examine the use of Nordbord across all football (soccer) levels and present practical recommendations concerning its application and potential limitations as a tool for measuring eccentric strength of the knee flexors (ESKF) incorporating the critical role of hamstring eccentric strength (HES) in injury prevention and performance enhancement. Twenty-nine studies were identified and met the inclusion criteria. The review shows that although Nordbord has potential as a practical and cost-effective method of measuring HES, the findings on the validity and reliability are conflicting. Furthermore, the study highlights several topics where the Nordbord could be recommended to stakeholders, as a tool to assess post-match recovery, prevention of hamstring injuries, and rehabilitation, as well as used as a performance indicator for balance, sprint, and change of direction performance. However, the review showed that ESKFs could be affected by fatigue and training volume, therefore, there is a need for normative values for different ages, genders, levels, and positions. Furthermore, the need for standardized methods and normalized data gathering, are argued as pivotal points to establish the Nordbord as a valuable alternative to the isokinetic dynamometer.